The Correlation between Learning Styles and Academic Achievement among English as a Foreign Language (EFL) Undergraduates Utilizing VARK Survey - Marwah Meelad Algheetah (Journal of Libyan Academy Bani Walid, 2025)
The current study sought to identify the preferred learning style of English as a Foreign Language (EFL) learners and its effect on their academic achievement at Bani-Waleed University. The study employed a quantitative correlational design. The participants consisted of 43 undergraduates majoring in English at Faculty of Arts from diverse academic levels. Fleming and Mills’ (1992) VARK survey was utilized as the tool for the study categorizing learners into four styles: Visual, Aural, Read/Write and Kinesthetic; those who prefer one learning style are regarded as unimodal while preferring two or more leaning styles are considered multimodal. Additionally, students’ Grade Point Average (GPA) was used as an indicator of participants’ academic performance. The findings revealed that most of the students prefer unimodal learning style, with kinaesthetic being the most prevalent model. Moreover, the results showed a significant correlation between the students’ learning style and their GPA, with moderate achievers favouring a unimodal type, whereas low achievers tended to prefer multimodal learning. The study emphasizes the importance of recognizing the diversity of learning styles. It also recommends that adapting teaching techniques to address varied learning preferences in EFL instruction would enhance the willingness for active participation in classroom, and thereby can boost their academic success.